PENGARUH MENTALITAS KWIRAUSAHAAN, LINGKUNGAN KELUARGA DAN TEMAN SEBAYA TERHADAP MINAT BERWIRAUSAHA DIKALANGAN MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS SILIWANGI (Survei pada Mahasiswa Pendidikan Ekonomi Universitas Siliwangi Angkatan 2021-2022) - Novia Pebrianti; Raden Roro Suci Nurdianti; Rendra Gumilar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The problem in this study is the low level of entrepreneurial interest among students, despite the vast potential and opportunities in entrepreneurship. This study aims to examine the influence of entrepreneurial mentality, family environment, and peers on the entrepreneurial interest of Economics Education students at Universitas Siliwangi, class of 2021–2022. The research employed a quantitative method with multiple linear regression analysis. The results show that, partially, entrepreneurial mentality (t = 4.222; sig. = 0.000), family environment (t = 2.953; sig. = 0.004), and peers (t = 2.052; sig. = 0.042) have a significant influence on entrepreneurial interest. Simultaneously, the three variables also have a significant influence (F = 34.171; sig. = 0.000). The coefficient of determination (R²) is 0.433, indicating that 43.3% of the variation in entrepreneurial interest is explained by these variables, while the remaining 56.7% is influenced by other factors not examined in this study.